Influence of Cash Waqf on Economic Growth Evidence from Malaysia - Ramli, Mona Fairuz; Shaari, Mai Syaheera M.; Bakhri, Boy Syamsul (Journal of Finance and Islamic Banking, 2022)
This paper proposes to look into the connection between Malaysian economic growth and cash waqf. This research makes use of time series data from the World Bank’s development indicators covering the years 2013 to 2019. To analyse both the long-term as well as short-term relationships between Malaysia’s cash waqf and the country’s economic growth, this research used the Autoregressive Distributed Lag (ARDL) model for cointegration and the Error Correction Model (ECM). Furthermore, the data indicates that while cash waqf has a short-term negative impact on economic growth, it possesses a favourable long-term impact from 2013 to 2019. Cash waqf is gradually becoming a tool for improving social well-being, lowering poverty rates and assisting in economic growth in the long run. Hence, the results portray a strong government supporting the importance of strengthening the waqf distribution policy to improve economic growth by raising awareness among financial institutions about the importance of philanthropy in cash waqf management and distribution. The ARDL model for cointegration and the ECM are used to assess both short- and long-run relationships in this research to add to the body of knowledge with regard to economic growth and cash waqf in Malaysia.